1996
DOI: 10.1007/bf02247327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ceruletide on perioral movements and the dopamine receptor-adenylate cyclase system in rats chronically treated with fluphenazine

Abstract: The effects of repeated administration of ceruletide (100 micrograms/kg/perday, i.p. for 3 days) on perioral movements and the striatal dopamine receptor adenylate cyclase system were examined in rats chronically treated with fluphenazine enanthate (FPZ) (25 mg/kg i.m. every 3 weeks for 30 weeks) and sesame oil-treated (control) rats. After the tenth injection of fluphenazine, the rats started to display five types of perioral movements (teeth chattering, chewing, tongue protrusion, mouth opening and perioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Another study showed that ceruletide, administered 24 h prior to the dopamine D 1 -receptor agonist SKF 38393, attenuated SKF 38393-induced grooming behavior in rats (54). Studies in animal models of dyskinesia also reported similar long-lasting effects of ceruletide (3,74,75), as described later in this review.…”
Section: Effects On Dopamine-mediated Behaviorssupporting
confidence: 58%
See 2 more Smart Citations
“…Another study showed that ceruletide, administered 24 h prior to the dopamine D 1 -receptor agonist SKF 38393, attenuated SKF 38393-induced grooming behavior in rats (54). Studies in animal models of dyskinesia also reported similar long-lasting effects of ceruletide (3,74,75), as described later in this review.…”
Section: Effects On Dopamine-mediated Behaviorssupporting
confidence: 58%
“…Chronic treatment with the antipsychotic drug fluphenazine produced perioral movements in rats, together with increases in dopamine D 1 receptor binding and dopamine-receptor-coupled adenylate cyclase activity in the striatum (3). Repeated administration of ceruletide for 3 d abolished the perioral movements and reversed the increases in both D 1 -receptor binding and dopamine-stimulated adenylate cyclase activity to the control level.…”
Section: Models Of Dyskinesiamentioning
confidence: 95%
See 1 more Smart Citation
“…There are several studies that support the findings of these experiments (Boyce et al, 1990a). In particular, the effects of repeated administrations of a CCK agonist, ceruletide, on perioral movements and the striatal dopamine receptor adenylase cyclase (Ac) system (Ashizawa et al, 1996) support these findings. Although body movement is a less sensitive measure of motor activity than EMG, in rats chroniically treated with fluphenazine to produce repetitive oral tremor, ceruletide, a CCK agonist, produced a cessation of repetitive oral movements with an increase in dopamine receptor sensitivity and dopamine-sensitive Ac activity in the striatum.…”
Section: Discussionmentioning
confidence: 80%
“…An understanding of the mode of action of CCK is of importance, since: (1) it may further our understanding of hypothalamic control of muscle activity; and (2) as a reported dopamine modulator, it is a candidate in the management of musculoskeletal disorders such as tardive dyskinesia (Van Kampen et al, 1996), Parkinson's disease (Boyce et al, 1990a), and 1823 myofascial disorders (Ashizawa et al, 1996).…”
Section: Introductionmentioning
confidence: 99%